2009
DOI: 10.1007/s11912-009-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characteristics of gastrointestinal stromal tumors in the pediatric and young adult population

Abstract: Gastrointestinal stromal tumors (GISTs) typically occur late in life; however, there are also reports of these tumors in pediatric patients and young adults. This rare, but fascinating subset of GISTs, have distinct clinical-pathological and molecular deviations from their adult counterparts. The majority of pediatric GIST patients are female and often present with multi-focal tumors that are completely or partly epithelioid in nature. These young patients often have metastatic disease, but still follow a slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
(60 reference statements)
2
35
0
Order By: Relevance
“…NPTX1 , one of several human pentraxins expressed primarily in nervous tissue, has been linked to the induction of neural lineage (45). The identification of two neural genes is particularly intriguing as it has been well established that GIST have both smooth muscle and neural elements (46). The WTS results for both BEX1 and NPTX1 were confirmed by qRT-PCR in the xenografts from the study, and the induction of BEX1 by the drug combination was also confirmed in IM-sensitive GIST-T1 and IM-resistant GIST430 cell lines, providing cellular models for exploring this finding.…”
Section: Discussionmentioning
confidence: 99%
“…NPTX1 , one of several human pentraxins expressed primarily in nervous tissue, has been linked to the induction of neural lineage (45). The identification of two neural genes is particularly intriguing as it has been well established that GIST have both smooth muscle and neural elements (46). The WTS results for both BEX1 and NPTX1 were confirmed by qRT-PCR in the xenografts from the study, and the induction of BEX1 by the drug combination was also confirmed in IM-sensitive GIST-T1 and IM-resistant GIST430 cell lines, providing cellular models for exploring this finding.…”
Section: Discussionmentioning
confidence: 99%
“…others in vitro and in vivo (15,19) and express the most common type of mutation found in GISTs (i.e., KIT exon 11), which is involved in the pathogenesis of this disease (19). We investigated whether these GIST cells release exosomes enriched in oncogenic KIT.…”
Section: Gist-t1 Cells Constitutively Shed High Numbers Of Exosomes Ementioning
confidence: 99%
“…This similarity between GISTs and ICCs is further borne out by the expression of the KIT protein (also called CD117) in nonneoplastic ICC and most GISTs (11). The identification of a fundamental hallmark of the biology of GISTs (i.e., gain-of-function KIT mutations) resulted in the rapid transformation of the treatment paradigm for this tumor type (15,16). Small molecule tyrosine kinase inhibitors, most notably imatinib mesylate (also known as Gleevec), have been developed and were found to be effective in the treatment of GISTs (16)(17)(18).…”
mentioning
confidence: 99%
“…22,25,28 There is currently strong evidence to suggest that the majority of pediatric GIST is biologically distinct from the typical adult-type GIST, as they do not usually harbor receptor tyrosine kinase mutations. [43][44][45] Nonetheless, some pediatric GIST do show at least initial response to newer generation receptor tyrosine kinase inhibitor. 46 Furthermore, a subset of the KIT/PDGFRA wild-type pediatric GIST contain genetic aberrations in genes coding for the succinate dehydrogenase subunits-SDHB, SDHC, and SDHD, 47 and there may be targeted therapy available in the future.…”
Section: Neurofibromatosis 1-associated Gastrointestinal Stromal Tumomentioning
confidence: 99%